Analisis Analisis Kesesuaian dan Daya Dukung Wisata Pantai Kecinan Sebagai Kawasan Ekowisata Bahari di Desa Malaka, Kabupaten Lombok Utara - Maulita Syahdina; Sitti Hilyana; Mahardika Rizqi Himawan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Kecinan Beach is a beach that has a fairly sloping beach topography with white sand. Kecinan Beach has beach tourism activities that have potential and attractiveness for visitors. This study aims to determine the suitability and carrying capacity of beach tourism in Kecinan Beach, Malacca Village, Pemenang District, North Lombok Regency. This study uses primary data conducted by survey methods and direct measurements in the field. The tourism suitability index value at station I is 92.86%, station II is 90.48% and station III is 85.71%, which means that the Kecinan Beach area is included in the very suitable category for beach tourism activities. The carrying capacity of the Kecinan Beach area with a beach length of 609 meters and an area that can be used for beach tourism is around 55,648 m2, which can accommodate as many as 2,225 people/day